2015
DOI: 10.3171/2014.10.peds14244
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive improvements following endovascular repair of vein of Galen malformation in a child

Abstract: Cognitive regression is a well-described presentation of vein of Galen aneurysmal malformations (VGAMs) in childhood. However, it remains unclear whether successful treatment of the malformation can reverse cognitive regression. Here, the authors present the case of a 5-year-old girl with a VGAM that was treated with staged endovascular embolization procedures. Comprehensive neurocognitive assessments were completed before intervention and approximately 6 years after initial presentation. There were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, previous reports may underestimate the rate of overall impairments. Indeed, only two studies have reported on the neuropsychological outcomes of VGAM, one describing outcomes of neonatal VGAM14 and the other a case of a child treated during her preschool years 15. Lecce and colleagues14 document good outcomes in around half of neonatal VGAM survivors, but a closer review of their data shows 74% of their sample had at least one poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, previous reports may underestimate the rate of overall impairments. Indeed, only two studies have reported on the neuropsychological outcomes of VGAM, one describing outcomes of neonatal VGAM14 and the other a case of a child treated during her preschool years 15. Lecce and colleagues14 document good outcomes in around half of neonatal VGAM survivors, but a closer review of their data shows 74% of their sample had at least one poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…If VGM is diagnosed in childhood or adolescence and treated appropriately, life expectancy increases significantly [13][14][15]. Emphasis is then placed on treatment of hydrocephalus and recurrent seizures and prophylaxis of intracranial hemorrhage, with the goal of allowing normal or quasi-normal neurological development [16,17]. Persistent venous hypertension with malabsorption of cerebral spinal fluid and initiation of intracranial hemorrhage due to secondary changes in venous outflow (including persistence of fetal falciform sinus, lack of development of the rectus sinus, or dilatation of the internal cerebral veins) are pathophysiological explanations for the exacerbation of symptoms [11,18,19].…”
Section: Clinical Symptoms and Challengesmentioning
confidence: 99%
“…If VGM is diagnosed in childhood or adolescence and treated appropriately, life expectancy increases significantly [12]. Emphasis is then placed on treatment of hydrocephalus and recurrent seizures and prophylaxis of intracranial hemorrhage, with the goal of allowing normal or quasi-normal neurological development [13]. Persistent venous hypertension with malabsorption of cerebral spinal fluid and initiation of intracranial hemorrhage due to secondary changes in venous outflow (including persistence of fetal falciform sinus, lack of development of the rectus sinus, or dilatation of the internal cerebral veins) are pathophysiological explanations for the exacerbation of symptoms [14].…”
Section: Introductionmentioning
confidence: 99%